Pro SQL server 2008 service broker - Aschenbrenner, Klaus (Berkeley, Calif. : Apress ; New York : Springer-Verlag [distributor], 2008)
Provides information on message-based programming and service-oriented database architecture using SQL Server 2008 Server Broker.
Includes index.
Keywords: SQL server; Client/server computing; Database management